Pengembangan Permainan Kartu UNO Berbasis Web Pada Materi Kimia Unsur Berintegrasi Kearifan Lokal Madura - Dwi Bagus Rendy Astid Putera; Wiwin Puspita Hadi; Siti Aisyah (Universitas Negeri Padang, 2022)
Learning by applying games will attract students attention. This research developed the UNO card game that used the concept of elemental chemistry, especially the main groups. Each card will have a bar code that contains information links related to the elements on the card. The product integrated with the values of Madura local wisdom. The process of making elemental chemistry UNO card media used the ADDIE development model. The trial was conducted on 25 students of class XII in one of the MA and SMA in Sampang and Pamekasan districts. The results of the validation of the UNO card for chemistry elements in the media aspect obtained an average of 96.09 (very valid) and the material aspect obtained an average of 91.70 (very valid). very good category with a value of 93 percent ease of obtaining indicators, 91 percent interest, and 87 percent usefulness. The results of the average percentage of high school students’ responses after using the elemental chemistry UNO card media obtained a very good category with an indicator value of 79 percent ease of obtaining, 80 percent interest, and 84 percent usefulness. Elementary chemistry UNO card learning media can make it easier for students to learn elemental chemistry.